BIM Research Trends in the Americas: A Systematic Literature Review - Cano Condori, Harold (LACCEI, 2025)
The objective of this review is to thoroughly examine the characteristics of research related to BIM (Building Information Modeling) in the Americas over the past five years. Two classifications were used for this purpose: the first divided the articles into theoretical and application-based studies, while the second classification considered 12 categories. These categories were established based on the clustering of the main topics and trends identified, using a clustering analysis. The search and selection of articles were conducted using the SCOPUS database and the PRISMA methodology. The findings revealed that the most researched topics in the Americas related to the BIM methodology are “data integration” studies, which aim to incorporate complementary information into BIM, such as climate data, virtual reality, and others, and “specific projects,” which focus on the specific applications of BIM in case studies. These categories represent 23.88% and 16.42% of the total, respectively. In third place, the category “people” was identified, which includes research evaluating the human factor, accounting for 13.43% of the total.